Dirk Hartog Island 'Return to 1616' Project – The first six years (2014 to 2019). (12th October 2020) - Algar, Dave; Morris, Keith; Asher, John; Cowen, Saul
Summary: Early European land use of Dirk Hartog Island left a legacy of cats, sheep and goats that led to the local extinction of 10 of the Dirk Hartog Island's 13 mammal species. A successful programme of eradication of these introduced species has resulted in improved habitat quality and is allowing the translocation of the island's locally extinct native mammals. The island could potentially support one of the most diverse small‐medium‐sized terrestrial mammal assemblages in Australia and contribute significantly to their long‐term conservation.